# algebra

6sqrt (2) - 3sqrt (7) = ???

1. 👍 0
2. 👎 0
3. 👁 37
asked by laura
1. 6sqt(2) - 3sqrt(7) = 0.548027441.

1. 👍 0
2. 👎 0
posted by Henry

## Similar Questions

1. ### Pre-Cal(Please help)

Find (a) f X g , (b) g X f, and (c) f X f f(x) = 3sqrt x-1 g(x) = x^3 + 1 For the f(x) the 3 is little above the sqrt sign. my answers were: (a) = 3sqrt x^4 -1 (b) = x^4 -1 (c) = 6sqrt x+1 These answers are wrong but I do not know

asked by Hannah on March 25, 2010
2. ### Pre-Cal

Find (a) f X g , (b) g X f, and (c) f X f f(x) = 3sqrt x-1 g(x) = x^3 + 1 For the f(x) the 3 is little above the sqrt sign. my answers were: (a) = 3sqrt x^4 -1 (b) = x^4 -1 (c) = 6sqrt x+1 These answers are wrong but I do not know

asked by Hannah on March 25, 2010
3. ### Algebra

Square roots. Woohoo. Want to check some work I did. 1. Perform indicated operations 3sqrt+2sqrt-sqrt 3sqrt+2sqrt[3*9]-sqrt[2*6] 3sqrt+3*2sqrt-2sqrt 3sqrt+6sqrt-2sqrt = 7sqrt 2.Simplify

asked by John on November 6, 2007
4. ### algerba

which is the simplest form of the radical expression sqrt (10)+6sqrt(10)+-3sqrt(10)

asked by ana on July 12, 2010
5. ### Algebra - sqrts

Square roots. Woohoo. Want to check some work I did. 1. Perform indicated operations 3sqrt+2sqrt-sqrt 3sqrt+2sqrt[3*9]-sqrt[2*6] 3sqrt+3*2sqrt-2sqrt 3sqrt+6sqrt-2sqrt = 7sqrt 2.Simplify

asked by John on November 6, 2007
6. ### Pre-Cal

Find f X g , g X f , and f X f f(x) = 3sqrt x-1 g(x) = x^3 + 1 For f(x) the 3 is little above the sqrt sign. My answers were: f(g(x)) = 3sqrt x^3 + 1 -1 g(f(x)) = 3sqrt (x-1)^3 -1 f(f) = 3sqrt x-1-1 My teacher said these were

asked by Hannah on March 29, 2010
7. ### Pre-Cal(Urgent)

Find f X g , g X f , and f X f f(x) = 3sqrt x-1 g(x) = x^3 + 1 For f(x) the 3 is little above the sqrt sign. My answers were: f(g(x)) = 3sqrt x^3 + 1 -1 g(f(x)) = 3sqrt (x-1)^3 -1 f(f) = 3sqrt x-1-1 My teacher said these were

asked by Hannah on March 29, 2010
8. ### Pre-Cal

Find f X g , g X f , and f X f f(x) = 3sqrt x-1 g(x) = x^3 + 1 For f(x) the 3 is little above the sqrt sign. My answers were: f(g(x)) = 3sqrt x^3 + 1 -1 g(f(x)) = 3sqrt (x-1)^3 -1 f(f) = 3sqrt x-1-1 My teacher said these were

asked by Hannah on March 29, 2010
9. ### Math(Please check)

Find f X g , g X f , and f X f f(x) = 3sqrt x-1 g(x) = x^3 + 1 For f(x) the 3 is little above the sqrt sign. My answers were: f(g(x)) = 3sqrt x^3 + 1 -1 g(f(x)) = 3sqrt (x-1)^3 -1 f(f) = 3sqrt x-1-1 My teacher said these were

asked by Hannah on March 30, 2010
10. ### calculus

Consider the function f(x)=6sqrt(x)+1 on the interval [3,5] . Find the average or mean slope of the function on this interval. I FOUND THIS: (6sqrt(5)-6sqrt(3))/2 By the Mean Value Theorem, we know there exists a c in the open

asked by John on July 13, 2010

More Similar Questions